IP accidents : negligence liability in intellectual property - Goold, Patrick Russell, 1987- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
In the twenty-first century, it has become easy to break IP law accidentally. The challenges presented by orphan works, independent invention or IP trolls are merely examples of a much more fundamental problem: IP accidents. This book argues that IP law ought to govern accidental infringement much like tort law governs other types of accidents. In particular, the accidental infringer ought to be liable in IP law only when their conduct was negligent. The current strict liability approach to IP infringement was appropriate in the nineteenth century, when IP accidents were far less frequent. But in the Information Age, where accidents are increasingly common, efficiency, equity, and fairness support the reform of IP to a negligence regime. Patrick R. Goold provides the most coherent explanation of how property and tort interact within the field of IP, contributing to a clearer understanding of property and tort law and private law generally.
Introduction -- Accidents -- History -- Efficiency and Equity -- Fairness -- Negligence -- Conclusion (on property, tort, and IP).
Title from publisher's bibliographic system (viewed on 24 Jan 2022).
Keywords: Intellectual property infringement -- Law and legislation; Negligence; Strict liability